Factors Effecting on Success of Agricultural Cooperative Enterprise in Islamabad Township - sara lorestani; homayoon moradnezhadi (تعاون و کشاورزی, 2019)
Abstract The purpose of this study was to factors effecting of success on Agricultural cooperative enterprise in Islamabad Township. The methodology of the research was descriptive correlation. The statistical population of the study was of 275worker Cooperative in Islamabad Township. By Using Cochran formula75 of them were selected as a statistical sample and studied by stratified random sampling method. The data a collection tool was a researcher-made questionnaire whose validity was confirmed by three faculty members from the Department of Entrepreneurship and Rural Development at Ilam University. The reliability of the questionnaire was 0.82 using Cronbach's alpha, which indicates that the reliability of the research tool was suitable. Data analysis in both descriptive and inferential statistics was performed using the SPSS21 software. The findings showed that the impact of cultural, social, economic, personal and human factors, infrastructure policy and management skills of the manager and board members was positive and significant. Multiple regression analysis showed that the two variables of the infrastructure policy and management skills were 42.3% of the variations in the dependent variable of the success of the cooperative businesses.